The padlock seat / Putri Aisyah Nadhirah Putramizan and Siti Rohaimini Yusoff - Putramizan, Putri Aisyah Nadhirah; Yusoff, Siti Rohaimini (2024)
The design of public spaces plays an essential role in safeguarding individual convenience and welfare, particularly in educational environments. These areas play a crucial role in determining the general feel and operation of a university campus. Including components like eco-friendly features, cosy seating configurations, and captivating designs helps to create a calm environment that is ideal for a range of activities. To further improve the overall experience, large, open spaces allow for the preservation of natural elements like sunshine and breeze. These public areas permit a variety of activities, such as busking, gaming, and healing techniques, in addition to acting as learning spaces. This allows them to meet the needs and interests of a wide range of people. Universities that carefully plan their public areas not only encourage a feeling of community and cooperation but also offer chances for leisure, recreation, and Universities that carefully plan their public areas not only encourage a feeling of belonging and teamwork, but they also offer chances for leisure, enjoyment, and personal development. These areas are essential gathering places for students where they may engage, educate themselves, and grow in a welcoming and encouraging setting.